LEARNING MODELS AND MEDIA EMPLOYED BY 7th GRADE ENGLISH TEACHERS - Nurmantara, Loga; Inderawati, Rita; Suganda, Lingga Agustina (Universitas Muhammadiyah Palembang, 2020)
Learning media and model are increasingly available in this 21st century era. However, many English teachers have not devised the sophisticated tools for learning.The aim of this study is to highlight the learning media and models used by English teachers to the 7th grade students in SMP Negeri 2 Sungailiat in the aspects of planning, implementing, and evaluating. Descriptive qualitative was used to get the data.The participants of this study were three teachers of SMP Negeri 2 Sungailiat who taught the 7th Grade Students. The instruments used were documentation, observation, and interview. The instrument of were adapted based on the Teacher Competency Assessment Tool (Instrument Penilaian Kemampuan Guru), and the result of documentation and observation were classified into four criteria. The findings showed that the teachers used learning model such as direct learning model and cooperative learning model. Meanwhile, the learning media used by the teachers were pictures, real object, whiteboard, textbooks, and example of written texts. The result of data analysis of documentation were classified that the three teachers made a learning plan included in the Good category with the final score 68%, and the result of observation were classified that the three teachers in carrying out learning activities included in the Good category with the final score 60%.